When proton pump inhibitors are compared, are there specific cases in which a certain proton pump inhibitors should be particularly preferred? - Çelebi, Altay; Yılmaz, Hasan (Turkish Journal of Gastroenterology, 2017)
Abstract Currently, proton pump inhibitors (PPIs) are widely used either over the counter or on prescription drugs. PPI’s are frequently used with other drugs when elderly and chronic desease burden population is taken to consideration. Drug interactions with PPIs are a prominent clinical problem in this direction. In this study, we reviewed potential risks of concomittant use of PPIs and other drugs and apropriate PPI choise. Cite this article as: Çelebi A, Yılmaz H. When proton pump inhibitors are compared, are there specific cases in which a certain proton pump inhibitors should be particularly preferred? Turk J Gastroenterol 2017;28(Suppl 1); S68-S70 Full Text Turkish